A review of recent experience (Paris, 1989)
This book introduce technical aspects of aquaculture. Marketing aspects of aquculture. Administrative aspects of aquaculture. Economic aspects of aquaculture.
Keywords: Nuôi trồng thủy sản,Aquaculture; Khía cạnh kinh tế,Economic aspects